Clonagem e caracaterização funcional do gene da DNA polimerase de trypanosma cruzi - Michelle Barbi de Moura (2008)
Cells are constantly exposed to endogenous or exogenous agents that cause injuries in DNA. These lesions can generate mutations or even lead to cellular death. A variety of repair mechanisms acts to maintain DNA integrity, but many lesions escape these processes leading to a replication fork blockage. To overcome this blockage, cells use a specialized group of DNA polymerases to bypass DNA lesions, restarting the replication forks and enhancing cell survival. This process is called translesion synthesis and is carried out by Y-family polymerases. Pol is member of this group and is able to bypass many type of lesions, as thymine-thymine dimer, AP sites and 8-oxoG. We report the cloning and characterization of the Pol gene (TcPol) from Trypanosoma cruzi, the causative agent of Chagas disease. This gene encodes protein containing motifs that are conserved between Y-family polymerases. In vitro assays showed that the recombinant protein is capable of synthesizing DNA in damage or undamaged primer-templates. Intriguingly, overexpression of TcPol does not increase resistance to UV light, cisplatin or zeocin, despite its ability to enhance UV resistance in a RAD30 mutant of Saccharomyces cerevisiae. T. cruzi overexpressing TcPol is also unable to restore growth after gamma irradiation, but T. cruzi cells overexpressing Pol are more resistant to treatment with hydrogen peroxide (H2O2). The results presented here suggest that TcPol plays an important role in the bypass of oxidative remanescent in DNA during S phase, stopping replication blockage.